A Dinner Engagement (1954) de Lennox Berkeley : un opéra-bouffe anachronique ? - Jean-Philippe Heberlé (Revue LISA)
Commissioned by The English Opera Group, written on a libretto by Paul Dehn and created at the Aldeburgh Festival on 17 June 1954, A Dinner Engagement is a comic opera by Lennox Berkeley (1903-1989). The instrumentation follows that of Benjamin Britten’s The Rape of Lucretia and Albert Herring. As regards Albert Herring, it served to a certain extent as a model for Berkeley’s opera as is illustrated by the way the text was set to music, by the use of the repetition of musical motifs, etc. A Dinner Engagement’s musical language is essentially tonal and the structure of the work is akin to a number opera. Musically speaking, the opera of the British composer is closer to some operas by Britten, Menotti and Poulenc than to works by Berg, Schoenberg and the composers of the European avant-garde of the 1960s. The musical tensions between vernacular and extra-vernacular elements foreground the difficulty of defining what an English opera is, most particularly at a time when Benjamin Britten tried to renew English opera.